2018
DOI: 10.1002/pd.5281
|View full text |Cite
|
Sign up to set email alerts
|

Novel usage of microfocus computed tomography (micro‐CT) for visualisation of human embryonic development—Implications for future non‐invasive post‐mortem investigation

Abstract: What's already known about this topic? Accurate pathological assessment of small gestational age fetuses is challenging. Dating an embryo/fetus is essential to recognise expected human developmental stages and prevent misdiagnosis. What does this study add? Micro‐CT offers a non‐destructive, digital method for dating human embryos. The micro‐CT imaging here is of the earliest gestation human embryo published to date with corresponding pathology. It can provide an alternative to autopsy even at early stages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…16,26 We have demonstrated a change in our clinical practice over 3 years as a result of regular imaging and increased confidence in the imaging results. Although the smallest fetus in this study cohort was at 11 weeks' gestation, we have previously reported imaging feasibility to be as low as 7 weeks' gestation, 27 thereby widening the possible inclusion case criteria.…”
Section: Discussionmentioning
confidence: 99%
“…16,26 We have demonstrated a change in our clinical practice over 3 years as a result of regular imaging and increased confidence in the imaging results. Although the smallest fetus in this study cohort was at 11 weeks' gestation, we have previously reported imaging feasibility to be as low as 7 weeks' gestation, 27 thereby widening the possible inclusion case criteria.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 Furthermore the detection of fetal anomalies may move even earlier with advances in transvaginal imaging and operator experience 27 especially as novel imaging technologies are facilitating excellent post-mortem examination even in very small fetuses. 28 One might have expected that the place of fetal ultrasound in prenatal diagnosis will be diminished with the rapid advances being made with molecular genetic prenatal diagnosis. 29,30 Instead we are increasingly becoming aware of the role of accurate fetal imaging to define the fetal phenotype to improve the efficiency of molecular testing, 31 aid interpretation of complex sequencing results as we recognise that fetal phenotypes may differ from post-natal ones 32,33 and improve our understanding of fetal development.…”
Section: A Decade Of Fetal Ultrasoundmentioning
confidence: 99%
“…One study has reported this technique to have a sensitivity of 93.8% and specificity of 100%, in a cohort of 20 foetuses below 22 weeks gestation. It has even been possible to image the internal organs of small embryos as early as 7 weeks gestational age at a similar resolution to light microscopy (Figure ). In certain cases it may alter parental counselling and change the suspected antenatal diagnosis; such as in Bardet Biedl syndrome .…”
Section: Introductionmentioning
confidence: 99%
“…The similarity of internal detail obtained by micro‐CT imaging versus histopathology is clearly visible. Source: Reproduced with permission from Shelmerdine et al, Prenatal Diagnosis 2018…”
Section: Introductionmentioning
confidence: 99%